PERSEPSI MAHASISWA JURUSAN KOMUNIKASI DAN PENYIARAN ISLAM FAKULTAS USHULUDDIN, ADAB DAN DAKWAH IAIN BATUSANGKAR TENTANG PROFESI DAÔÇÖI - Chintia Arnita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The main problem in this research is the perceptions of students majoring in Islamic Communication and Broadcasting at the Faculty Ushuluddin, Adab and Dakwah IAIN Batusangkar class of 2017, 2018 and 2019 about the profession of DaÔÇÖi. The purpose of this discussion is to find out the perceptions of students majoring in Islamic Communication and Broadcasting , Faculty Ushuluddin, Adab and Dakwah IAIN Batusangkar class of 2017, 2018 and 2019 about the profession of preachers. This type of research is descriptive quantitative. Researchers conducted data collection techniques by distributing questionnaires to students of the 2017, 2018 and 2019 class KPI majors with a total sample of 45 people, which is by providing a set of questions that have provided answers related to the perceptions of KPI majors about the DaÔÇÖi profession. The result of the research obtained by the perceptions of students majoring in Islamic Communication and Broadcasting at the Faculty Ushuluddin, Adab and Dakwah IAIN Batusangkar class of 2017, 2018 and 2019 about the DaÔÇÖi profession were 37,8% and 86,7% of the factors the researchers examined. This means that the perception of IAIN Batusangkar Islamic Communication and Broadcasting students about the DaÔÇÖi profession which is viewed from 2 indicators (worldly and ukhrawi) is that they disagree with the statement that DaÔÇÖi is a humble/ lowly profession and agrees with the statement that DaÔÇÖi is a guide to the path of kindness.